2010
DOI: 10.1152/ajpgi.00101.2010
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal potassium efflux mediated via Kcnn4 channels provides the driving force for electrogenic anion secretion in colon

Abstract: Intermediate conductance K(+) (Kcnn4) channels are present in both mucosal and serosal membranes of colon. However, only serosal Kcnn4 channels have been shown to be essential for agonist-induced (cAMP and Ca(2+)) anion secretion. The present study sought to determine whether mucosal Kcnn4 channels also play a role in colonic anion secretion. Mucosal-to-serosal and serosal-to-mucosal unidirectional (86)Rb (K(+) surrogate) fluxes as well as short-circuit current (I(sc); a measure of anion secretion) were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Moreover, stimulation of the rat pancreas with secretin caused a marked increase in K + concentrations in the pancreatic juice, which was equal to twice that in the plasma, indicating that K + was secreted 25 . K + efflux was also shown to be mediated via mucosal K Ca 3.1 channels in other epithelia, such as the distal colon, and provided, in part, the driving force for agonist-induced anion secretion 26 . Another example is salivary acini, in which both K Ca 1.1 and K Ca 3.1 were shown to be expressed on the apical membrane and contribute to optimal secretion 27 .…”
Section: Kcnn4 (Kca31 Ik Sk4)mentioning
confidence: 96%
“…Moreover, stimulation of the rat pancreas with secretin caused a marked increase in K + concentrations in the pancreatic juice, which was equal to twice that in the plasma, indicating that K + was secreted 25 . K + efflux was also shown to be mediated via mucosal K Ca 3.1 channels in other epithelia, such as the distal colon, and provided, in part, the driving force for agonist-induced anion secretion 26 . Another example is salivary acini, in which both K Ca 1.1 and K Ca 3.1 were shown to be expressed on the apical membrane and contribute to optimal secretion 27 .…”
Section: Kcnn4 (Kca31 Ik Sk4)mentioning
confidence: 96%
“…KCa3.1a appears to be found in smooth muscle [49] . Further, Kumar et al reported that agonist-dependent activation of KCa3.1c stimulated anion secretion in the rat distal colon and suggested that KCa3.1c may contribute to the stool K + losses associated with diarrheal illnesses [50] . Additional physiological roles of the splice variants of KCa3.1 will be unraveled by further investigations.…”
Section: Intermediate-conductance Kca Channel (Kca31)mentioning
confidence: 99%
“…Later in 2011, CORM-2, a CO donor, was also found to evoke chloride and HCO 3 − currents across the apical membrane of rat distal colon, which is blocked by another nonspecific anion blocker glibenclamide 14 . Given that HO-1 is ubiquitously distributed and apical CFTR is present in rat distal colon 4043 , endogenous CO might be a physiological modulator of CFTR channel currents. It is interesting to employ CFTR-specific inhibitor CFTRinh172 to examine whether the CO gas increases CFTR activity by releasing inhibitive Fe 3+ from the ICL3-R interface and whether the CO effect is repeated and whether CO enhances Cl − secretion of CF-causing mutants by airway epithelial cells (Figure 1) 44 .…”
Section: Cftr Channelmentioning
confidence: 99%